Integration of Capacitor Coupled Substation and Controllable Network Transformer for Bidirectional Power Flow and Grid Control - Nene, Sinqobile Wiseman (Current Approaches in Engineering Research and Technology Vol. 10, 2024)
Electricity distribution in sparsely populated areas presents economic challenges due to conventional distribution infrastructure costs. This study proposes the integration of Capacitor Coupled Substations (CCS) with Controllable Network Transformers (CNT) to enable bi-directional power flow and flexible grid control for rural electrification and microgrid integration. Using MATLAB/Simulink, the CCS-CNT system was modeled to evaluate its impact on transmission networks and voltage stability. Simulation results demonstrate negligible voltage disturbance when connecting CCS-CNT to a 400kV/11kV network, with output voltage maintained within acceptable limits. Additionally, the system shows the potential to eliminate the need for external ferroresonance suppression circuits. These findings suggest that CCS-CNT systems could offer a cost-effective solution for power tapping and injection in underserved areas, enhancing both grid resilience and energy access.